2017
DOI: 10.1371/journal.pone.0188395
|View full text |Cite
|
Sign up to set email alerts
|

Ex-vivo quantitative susceptibility mapping of human brain hemispheres

Abstract: Ex-vivo brain quantitative susceptibility mapping (QSM) allows investigation of brain characteristics at essentially the same point in time as histopathologic examination, and therefore has the potential to become an important tool for determining the role of QSM as a diagnostic and monitoring tool of age-related neuropathologies. In order to be able to translate the ex-vivo QSM findings to in-vivo, it is crucial to understand the effects of death and chemical fixation on brain magnetic susceptibility measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 49 publications
4
16
0
Order By: Relevance
“…Our results were consistent with previous findings in that we also observed a steep reduction in R 2 * after washing out formalin with PBS which was, however, not accompanied by a corresponding QSM offset, but by a decrease in QSM variability. These results are partially consistent with another study that found no effect of formalin fixation on bulk tissue susceptibility . These observations, supported by results from our vial experiment (Figure ; Supporting Information Table ), suggest that the short‐T 2 * behavior of the formalin solution used in the present study might not have been driven by its magnetostatic properties alone.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results were consistent with previous findings in that we also observed a steep reduction in R 2 * after washing out formalin with PBS which was, however, not accompanied by a corresponding QSM offset, but by a decrease in QSM variability. These results are partially consistent with another study that found no effect of formalin fixation on bulk tissue susceptibility . These observations, supported by results from our vial experiment (Figure ; Supporting Information Table ), suggest that the short‐T 2 * behavior of the formalin solution used in the present study might not have been driven by its magnetostatic properties alone.…”
Section: Discussionsupporting
confidence: 93%
“…These results are partially consistent with another study that found no effect of formalin fixation on bulk tissue susceptibility. 55 These observations, supported by results from our vial experiment (Figure 7; Supporting Information Table S3), suggest that the short-T 2 * behavior of the formalin solution used in the present study might not have been driven by its magnetostatic properties alone. An alternative explanation, supported by a previous microwave spectroscopy study, 56 is that the formaldehyde molecule has counteracting paramagnetic and diamagnetic components at the microscopic level, although this is only a hypothesis at present time.…”
Section: Discussionsupporting
confidence: 78%
“…38 Future studies using in vivo carotid QSM are needed to clarify the usefulness of the in vivo imaging. Evia et al 39 showed the strong linear correlation in susceptibility on QSM between in vivo and ex vivo brain tissues. Therefore, our results may be valuable for translation of ex vivo QSM findings to in vivo ones.…”
Section: Discussionmentioning
confidence: 99%
“…The time from fixation of samples to MR imaging was relatively long; the mean time was 36 days. Evia et al 39 reported that susceptibility in gray and white matter measured ex vivo with QSM does not change in the first 6 weeks after death and fixation. Therefore, the effect of the time from fixation to MR imaging may have been small.…”
Section: Discussionmentioning
confidence: 99%
“…However, Evia et al showed that the magnetic susceptibility measurements of the same participants between in vivo and fixed ex vivo brains immersed in PBS can be modeled as a linear function. 37 Our previous study showed that collagen fibers in the cartilage have anisotropic susceptibility under physiological conditions. Therefore, we expect that a linear correlation between MSA and fibrosis still exists in physiological conditions, although the correlation coefficient may be altered by fixation.…”
mentioning
confidence: 98%